Pengaruh Hypnotherapy Terhadap Intensitas Nyeri pada Ibu Post Sectio Caesarea di RSUD DR H.M Rabain Muara Enim Tahun 2024 - Muniarni, Yanis; Hairunisyah, Rika; Novita, Nesi (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
WHO data and the Global Survey on maternal and Perinatal Health in 2021 amounted to 46.1% of all section cesarean births. Indications for section cesarea were mostly due to complications with a percentage of 23.2%. Sectio caesarea surgery causes pain and limitation in movement. One of the therapies to overcome postoperative pain after cesarean section is to do hypnotherapy. The study aims to determine the effect of Hypnotherapy on pain intensity in post Sectio Caesarea mothers at Dr. H.M Rabain Muara Enim Hospital in 2024. This study used a quasi experimental method with a one group pre test-post test design. The study was conducted in April-May 2024 with a population of all mothers post Sectio Caesarea who were treated at URK RSUD Dr. H.M Rabain Muara Enim as many as 27 respondents taken by accidental sampling method. Data analysis using the willcoxon test. In this study obtained the pain scale of post sectio caesarea patients before being given hypnotherapy most respondents experienced moderate pain as many as 20 respondents (74.1%), while after hypnotherapy most respondents experienced mild pain as many as 20 respondents (74.1%). The results of statistical tests with Wilcoxon obtained a value of p.value = 0.000 means that there is a difference in pain intensity before and after Hypnotherapy in post Sectio Caesarea mothers. Based on the research, it is concluded that there is an effect of hypnotherapy on pain intensity in post sectio caesarea mothers at Dr. H.M Rabain Muara Enim Hospital in 2024.